Greening economies in partner countries: Priorities for international cooperation - Tilman Altenburg; Anna Pegels; Mauricio Böhl Gutierrez; Clara Brandi; Hanna Fuhrmann-Riebel; Franco Jauregui Fung; Daniele Malerba; Babette Never; Andreas Stamm; Rita Strohmaier; Ulrich Volz (German Institute of Development and Sustainability (IDOS), 2024)
While polluting industries are still flourishing, the green economy is on the rise. In low- and middle-income countries, the resulting opportunities are mostly underexplored. The Federal Ministry for Economic Cooperation and Development (BMZ)'s new strategy for 'Sustainable economic development, training and employment' shifts gears towards a green and inclusive structural transformation, recognising that only a just transition approach with credible co-benefits for societies can gain societal acceptance (BMZ, 2023). It is now essential to provide evidence of how a greener economy can offer direct economic benefits to national economies and the majority of their citizens. Ongoing cooperation portfolios need to be adjusted to this new and timely orientation in the BMZ's core strategy. We suggest focusing on the following six areas: Eco-social fiscal reform should be a priority area in at least 15 of the over 40 partner countries with whom Germany cooperates on 'sustainable economic development', systematically linking revenues from pricing pollutions to pro-poor spending. Development policy should promote inclusive green finance (IGF) through market-shaping policies, such as an enabling regulatory framework for the development of digital IGF services and customer protection in digital payment services. It should also build policymakers' capacity in developing IGF policies and regulation. Support in the area of sustainable, circular con-sumption should focus on eco-design, and repair and reuse systems. It should build systems design capa-cities and behavioural knowledge, to integrate con-sumers in low-carbon and circular industry-consumer systems. This will need new collaborations with actors shaping systems of consumption and production, for instance with supermarkets or the regulators of eco-design guidelines. Germany should strategically support national hydro-gen strategies, including a just transition approach and prioritising green over other 'colours' of hydrogen. This means strengthening industrial policy think tanks, technology and market assessment agencies, technology-related policy advice as well as skills development, and exploring distributive mechanisms to spread the gains and ensure societal acceptance. Sustainable urbanisation should be a more explicit priority, given its potential for job creation and enterprise development. This means supporting partners in integrating land-use, construction and mobility planning for compact, mixed-use neighbourhoods, and anti-cipating green jobs potential and skills required within cities. Lastly, Germany should support green industrial policy and enlarge policy space in trade rules by promoting the core institutions of industrial policy, for example, technology foresight agencies, coordinating platforms for industry upgrading, and policy think tanks, and working towards reforms of the trading system, such as rules to allow clearly defined green industrial subsidies, preferential market access for green goods and services from low-income countries, or technology transfer. It is evident for all areas that the challenges in low- and middle-income countries will differ from those in high-income countries. It is, therefore, imperative that successful programmes are co-developed with local partners. A just green transition that harvests benefits beyond a healthier environment and is supported by societies will then be achievable.
Keywords: 320; Green industrial policy; structural transformation; development policy; green growth; green finance; eco-social fiscal reform; sustainable cities; sustainable consumption; green trade; green hydrogen